Infant mortality on Sri Lankan Plantations from 1887 - 1985. - Perera, R.S (My University, 1987)
The infant mortality rate is used as a sensitive indicator of the health of the resident plantation population.This dissertation attemps to describe the pre-1974 period as well as the rapid improvement thereafter.Medical facilities are provided on estates mostly through a dispensary. Some estates have a maternity home and a few have a hospital which consists of a maternity ward, a male and a female ward. A few registered medical practitioners and assistant medical practitioners work on estates.But most estates employ who are medically unqualified.Most midwives are government -trained and registered but some estates still employ unqualified midwives.A new cadre of plantation family welfare supervisors perform liasion activities between the medical staff and the workers.Other functions include maintenance of enviromental sanitation motivation for family planning and health education.